Evidence Of System: Part II - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 1978)
As there is legislative provision for the admission of evidence of system in Malaysia it would seem to be unnecessary for the courts to rely on English authorities. However as we have seen in the case of Public Prosecutor v Ong Kok Tan the Federal Court held that the principles laid down in Makin v Attorney General of New South Wales are embodied in section 15 of the Evidence Act. Similarly in the case of Datuk Haji Harun bin Haji Idris v Public Prosecutor Counsel for the appellant in his argument on the subject of evidence of system paraphrased the judgment in Makin's case.